Antagonistic activity of rhizobacteria in the inhibition of the fungus Pseudocercospora griseola (Sacc.) - de Oliveira, Tayla Évellin; Resende, Maria de Lourdes; Florentino, Ligiane Aparecida; Dias e Silva, Nhayandra Chistina (Científica, 2020)
The angular leaf spot caused by the fungus Pseudocercospora griseola (Sacc.) is one of the main diseases in bean plants. Considering the losses caused by this disease, rhizobacteria may be an alternative for the management of this phytopathogen. Thus, this study evaluates the potential of different strains of rhizobacteria in the inhibition of the fungus P. griseola (Sacc.). The antagonistic effect of twenty bacterial strains on this phytopathogen was studied using the circle technique. The completely randomized experimental design was used with five repetitions. Evaluation was performed on the tenth day, when colony diameter was measured and the percentage of growth inhibition (PGI) of the pathogen was calculated. Twelve strains inhibited the mycelial growth of P. griseola (Sacc.), with PGI values above 40% compared to the control. The strain UNIFENAS 03-36 stood out with inhibition percentage of 85.10%.